Dermoscopic changes in melanocytic nevi covered with both an opaque tape and sunscreen cream during narrowband ultraviolet B therapy - Derya Ök Kekeç (Mattioli1885, 2018)
Background: Ultraviolet (UV) light may cause dermoscopic changes on melanocytic nevi (MN).